PENYULUHAN TENTANG BAHAYA NARKOBA PADA REMAJA MELALUI PENDEKATAN EDUKASI AFEKTIF - Yuliati Yuliati; Rasianna Br. Saragih (Universitas Bengkulu, 2018)
Community service activities has a title “Guidance the Dangers of Drug for Teenager through Affective Education Approach”. The target of the community activities program are youth / high school students (SMA) 1 Talang Empat, Central Bengkulu Regency, Bengkulu Province. Activities carried out in SMA-N 1 Central Bengkulu aims to encourage young people, in this case school students to stay away from the dangers of drugs. Counseling methods with affective educational approach is deemed appropriate to be used for this approach is not only limited to providing information about the dangers of drugs alone but students are also stimulated to think about the values of life of their own and make a conclusion about whether the benefits of drug abuse in life. Affective aspects of education aimed at developing the personality, maturation itself, increase the ability in decisions making, knowing how to cope with the mental stress effectively. Students have a tendency to not want to get involved in drug abuse. In addition caused enough understanding that drugs only bring harm health and spend a lot of money, students also tend to choose friends who have the same background (students). Keywords: drugs, affective education, youth